Vadybininko informacinė elgsena organizacijoje: socialinių tinklų naudojimas - Janiūnienė, Erika (Information & Media, 2007)
Straipsnyje nagrinëjama vadybininko informacinë elgsena organizacijoje ir socialiniø tinklø naudojimas informacijos ieðkai. Darbe apibûdinama organizacijos aplinkos stebëjimo sistema ir pagrindiniai sistemos elementai, analizuojamas vadybininko informacinës elgsenos modelis ir informacinës elgsenos veiksniai. Apþvelgiamos vadybininko, kaip informacijos vartotojo, socialiniø tinklø naudojimo informacijos ieðkai prieþastys, trûkumai ir pranaðumai*.Managers information behaviour in an organization: use of social networksErika JaniūnienėSummaryA modern organization cannot exist as a closed system. It has to be in contact with the environment so as to conceive changes that occur outside the organisation and adjust to the ever-changing social and economic situation. Environmental scanning makes it possible for an organization to envisage development and improvement, to assess its market situation and ability to compete as well as to identify its business-related risks. In order to conceive its exposure to various factors and envisage its long-term prospects, an organization should at all times scan the environment.The environment may be defined as the totality of physical and social factors that have a direct impact on decision-making within an organization (Choo, 2002).The article deals with the conception and system of environmental scanning, giving special consideration to the analysis of information behaviour of the manager viewed as a user of information. The work examines the model of the manager’s information behaviour as well as the elements having an effect on information seeking, i.e. the manager’s role in an organization, the activity that he or she is engaged in, the context of information behaviour as well as the nature of problems to be resolved.Considering the importance of environmental scanning in the activity of an organization and the fact that the information behaviour is one of the components of environmental scanning, there are solid grounds to say that the manager’s information behaviour becomes a Critical Success Factor (CSF) in the activity of an organisation (Tibar, 2005) The manager’s proficiency in finding true and accurate information and making the most of it in decision-making contributes to the organization’s ability to pursue its goals and enhance its competitiveness on the market. Yet, in the emerging knowledge society, information seeking by the manager – a user of information – is being complicated by the ever-growing information flow within the organization as well as by the manager’s lack of skills and knowledge to cope with the task. In order to meet the demand for information and resolve the arising problems, managers most frequently make use of social networks. The article discloses the factors that force the manager to engage social networks in information seeking. It also gives an analysis of the related difficulties and benefits.